2011
DOI: 10.3109/02770903.2011.555031
|View full text |Cite
|
Sign up to set email alerts
|

Level of Parent–Asthmatic Child Agreement on Health-Related Quality of Life

Abstract: Our study illustrated that parents overestimate HRQoL of their children with asthma even though moderate agreement between child self-reports and parent proxy-reports on HRQoL was noticed. Fathers seem to be better proxy-reporters than mothers. Any evaluation of current approaches to measuring children's HRQoL needs to allow both parent and child to give their own perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 29 publications
(42 reference statements)
7
46
0
2
Order By: Relevance
“…Parental reports of wheezing are widely accepted in epidemiological studies and reliably reflect the incidence of wheezing in preschool children [30]. When children do not have the cognitive ability to report their own HRQOL, proxy reports by parents are appropriate sources of information about HRQOL [31]. Both overestimation and underestimation of HRQOL scores may have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Parental reports of wheezing are widely accepted in epidemiological studies and reliably reflect the incidence of wheezing in preschool children [30]. When children do not have the cognitive ability to report their own HRQOL, proxy reports by parents are appropriate sources of information about HRQOL [31]. Both overestimation and underestimation of HRQOL scores may have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…27 Besides, a high level of disagreement was observed between children's self-assessment and that of fathers, which is contradictory to what previous studies suggested that fathers served better as proxies than mothers. 29 However, that study was conducted among children with asthma, whose capabilities are not as limited as in our target population.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between child and parent reported quality of life improves with increasing age of the child (Annett et al, 2003). Although the agreement between child self-report and parent proxy report on health related quality of life has been showed as satisfactory, according to Petsios et al (2011), parents may overestimate health related quality of life of their children with asthma. This has to be taken into account when interpreting results from parent reported health related quality of life questionnaires, in comparison with child selfreports.…”
Section: Health Related Quality Of Life Instruments and Childhood Asthmamentioning
confidence: 99%
“…The most prominent asthma-specific health related quality of life questionnaires are the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) , the How Are You (HAY) (Le Coq et al, 2000) instrument and the Childhood Asthma Questionnaire (CAQ) (Christie et al, 1993). If children are unable to report about their own experience reliably, parents are appropriate sources of information about health related quality of life (Petsios et al, 2011). One study suggests that fathers may be better proxy reporters than mothers (Petsios et al, 2011).…”
Section: Health Related Quality Of Life Instruments and Childhood Asthmamentioning
confidence: 99%
See 1 more Smart Citation